Impact of Facebook sponsored advertisements on Egyptian youth’s attitudes and purchase intention - Nashwa Mohamed Ayman; Hanan Gunied; Asmaa El-Mously (Insights into Language, Culture and Communication)
This research paper is trying to examine the impact of Facebook sponsored advertisements on Egyptian youths’ attitudes and purchase intentions. It aims at exploring the relationship between Facebook sponsored advertisements’ personalization, perceived usefulness, perceived ease of use and consumers’ attitudes and purchase intentions. In addition to investigating the influence of age and gender on attitudes and purchase intention. The theoretical framework of this paper includes the Technology acceptance model. An online questionnaire was distributed through social media platforms with a sample of 417 young men and women who are Facebook users and their age is between 25-34 from Cairo and Giza. The findings showed that personalization, perceived usefulness and perceived ease of use have a positive influence on their attitudes and purchase intentions. The results also showed that attitudes mediate the relation between all these independent variables and purchase intentions, and are considered a factor that affect consumers’ purchase intentions. Also, it was found that there is no significant relation between gender and attitudes and purchase intentions, while those who are younger (25-30) had higher purchase intentions. Received: 14 January 2024 Accepted: 05 February 2024 Published: 16 May 2024